2020
DOI: 10.1371/journal.pone.0227309
|View full text |Cite
|
Sign up to set email alerts
|

Real-world data about emotional stress, disability and need for social care in a German IBD patient cohort

Abstract: To date, there is insufficient insight into inflammatory bowel disease (IBD)-associated stress, recognized disability, and contact with the social care system. We aimed to assess these parameters in IBD patients and a non-IBD control group, who were invited to participate in an online survey developed specifically for this study (www.soscisurvey.de) with the help of IBD patients. 505 IBD patients and 166 volunteers (i.e., control group) participated in the survey. IBD patients reported significantly increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The length of the questionnaires might be a barrier to patients' willingness to participate where some have used questionnaires consisting of 80 items. [37] The visual representation of the patient's functionality is thought to be an advantage of the IBD-Disk questionnaire although radar diagrams have been criticised. For instance, these graphs promote comparison between different axes on the same ordinal scale although a value of 6 on the "Regulating defecation" or "Abdominal pain" parameters might not be of equal bearing as "Body image" or "Energy" axes.…”
Section: Discussionmentioning
confidence: 99%
“…The length of the questionnaires might be a barrier to patients' willingness to participate where some have used questionnaires consisting of 80 items. [37] The visual representation of the patient's functionality is thought to be an advantage of the IBD-Disk questionnaire although radar diagrams have been criticised. For instance, these graphs promote comparison between different axes on the same ordinal scale although a value of 6 on the "Regulating defecation" or "Abdominal pain" parameters might not be of equal bearing as "Body image" or "Energy" axes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kubesch A. et al conducted an online survey in a German cohort of unselected IBD patients, focusing on overall emotional stress and the potential related factors, by using a questionnaire developed in cooperation with IBD patients. Results showed the presence of significant emotional stress but only 30% of the patients were in contact with the social care system and the corresponding support [31]. Factors such as sleep disorders, asthenia, and loss of appetite and weight, which often accompany the active course of IBD, could contribute to the onset or the worsening of pre-existing mood disorders [32].…”
Section: Discussionmentioning
confidence: 99%
“…Among the associations explored in this study, the greatest OR was found for the subsequent development of depression among IBD patients. This finding was not unexpected, given the psychological toll and worse quality of life from IBD disease burden 43 . Elevated depression risk among the unaffected siblings of IBD may reflect environmental stressors such as caregiver fatigue in addition to shared aspects of pathogenesis such as underlying genetic predisposition 44,45 .…”
Section: Discussionmentioning
confidence: 86%